With random actions towards inefficiency - the implementation of Norwegian youth sport policy through the 2016 Lillehammer Winter Youth Olympic Games - Strittmatter, A.-M.; Skille, E. A. (Conference: 23rd European Association for Sport Management Conference, Dublin 2015, 2015)
Mega and major sport events, especially the Olympics, are often assigned to be part of a national sport political agenda. In that respect, the 2016 Lillehammer Winter Youth Olympic Games (YOG) is defined as a part of the national youth sport policy defined by the Norwegian Olympic Committee and Confederation of Sports (NIF). NIF`s current policy is called "the youth campaign" and aims at increasing young people`s participation, regarding athletes, leaders and coaches (NIF 2014): The YOG is supposed to be the driving force to implement the youth sport policy. This paper scrutinizes how NIF`s objectives are practically pursued. The research question therefore is: How is the Norwegian youth sport policy implemented in connection with the YOG? With Random Actions towards Inefficiency - the implementation of Norwegian youth sport policy through the 2016 Lillehammer Winter Youth Olympic Games.